Kontribusi pendapatan usahatani terhadap ekonomi rumah tangga petani di daerah pedesaan : review - Mohammad Shoimus Sholeh; Luluk Mublihatin; Nur Laila; Siti Maimunah (Fakultas Pertanian Universitas Yudharta Pasuruan, 2021)
The majority of people in rural areas in their daily life work as farmers and rely on agricultural products to meet their daily needs. The problem is that the income from farming is not sufficient to meet daily needs. Therefore, it is necessary to study the contribution of farm income to total household income. The method used in this research is the literature review method. The results of several studies indicate that the characteristics of farmers in rural areas have an average primary school education (more than 50%), while the average age of farmers is still in the productive age. The average contribution value of rice farming from several studies with different areas from several research results is more than 50%, meaning that farmers depend on rice farming days to fulfill all their daily needs rather than relying on side jobs, while the contribution of tobacco farming from several research results from less than 50%. In calculating the contribution of many researchers who have not included time susceptibility, either yearly, seasonally, or monthly, this will affect the tabulation of the calculation of non-farm income.